Self-expandable metallic stent placement above the papilla without endoscopic sphincterotomy in patients with distal malignant biliary obstruction - Takada, Ryoji; Ikezawa, Kenji; Kiyota, Ryosuke; Imai, Toshihiro; Abe, Yutaro; Fukutake, Nobuyasu; Ashida, Reiko; Nawa, Takatoshi; Tabuchi, Takahiro; Katayama, Kazuhiro; Ohkawa, Kazuyoshi (Endoscopy International Open, 2020)
Background and study aims The best method for endoscopic placement of self-expandable metallic stents (SEMS) for distal malignant biliary obstruction (MBO) has not yet been determined. The aim of this study was to evaluate how SEMS placement above the papilla and without endoscopic sphincterotomy (EST) impacts the time to recurrent biliary obstruction (RBO) in patients with distal MBO.Patients and methods We retrospectively reviewed data for 73 consecutive patients with unresectable distal MBO who underwent endoscopic SEMS placement for the first time at our institution between April 2014 and March 2016. We compared time to RBO of SEMS placement above the papilla (intraductal placement) with SEMS placement across the papilla (transpapillary placement). In the intraductal placement group, we also compared time to RBO of placement without EST with placement with EST.Results Endoscopic SEMS placement was performed in 30 patients with intraductal placement and in 43 patients with transpapillary placement. The median time to RBO was significantly longer with intraductal placement (307 days) than with transpapillary placement (161 days) (P = 0.022). Complication rates did not differ between the two groups. In both univariate and multivariate analysis, intraductal placement was an independent factor contributing to prolonged time to RBO. In intraductal placement, time to RBO was significantly longer in SEMS placement without EST than with EST (363 days vs. 227 days, respectively; P = 0.026).Conclusions Intraductal SEMS placement, especially without EST for distal MBO contributed to longer time to RBO.